EUROPEANISATION OF TURKISH PUBLIC ADMINISTRATION IN THE EUROPEAN UNION NEGOTIATION PROCESS - H. Kutay AYTUĞ (Fırat University, 2019)
Europe has been an important reference for Turkish modernisation since Ottoman Empire. European values lay down the core of modern Turkey since the establishing of republic and have affected nearly all of transformations which have been realised in the social life and public administration. This article focuses on the Europeanisation of Turkish Public Administration after 2000s. For this purpose it starts with explaining of the conceptual and theoretical framework and clarifies the concepts of negotiation, Europeanisation, Multi-level Governance and European Administrative Space. Then it focuses on Europeanization of public administration in EU countries. For this purpose it summarises the historical background of Europeanization of public administration in Greece and Poland. After that to show the transformation of Turkish public administration, it is given a short summary on the institutional transformation between 1963and 1999 when is date of Helsinki Summit which declared Turkey as candidate country. Later, it gives a very detailed summary on institutional and legislation reform in Turkey after 2000. In this chapter, firstly it is focused these reforms, which target to fulfil Copenhagen Political Criteria, are realised between 1999 and 2005 via Regular Reports on Turkey’s Progress towards Accession which are written European Commission and official documents of Republic of Turkey Ministry for EU Affairs. Afterwards it reveals transformation process on Turkish Public Administration and opening Chapters of Acquis Communautaire during negotiation process after October 2005. Finally this article argues that the negotiation process between Turkey and EU which nearly freeze after 2010 will continue by accelerating due to Syria Crisis and immigrants going to EU countries via Turkey.